The Relationship between Chlorite and Reservoir Quality in the Huagang Formation, Xihu Depression, China - Dongping Duan; Xianguo Zhang; Binbin Liu; Jianli Lin; Wenguang Wang (Energies, 2022)
Low permeability tight gas resources account for 90% of the Xihu Sag. Under the background of extensive development of low permeability and tight reservoirs, the key to economic and effective development is to find sweet reservoir formation. To clarify the origin and distribution of a sweet reservoir in the study area, it is important to study the formation and evolution mechanisms of chlorite. In this study, based on the analysis of thin section, X-ray diffraction and SEM, through the analysis of the key factors in the formation of authigenic chlorite of the Huagang Formation in the middle and north of the central inversion structural belt, we reasoned the formation and evolution process of chlorite in the whole life cycle. According to the sedimentary diagenetic response characteristics of chlorite, two types of favorable sedimentary facies belts of chlorite are identified. The results showed that the development of pore-lined chlorite is a natural advantage of reservoirs in the East China Sea. Chlorite is formed under the joint action of three factors: the source of iron and magnesium ions, the alkaline environment in the early diagenetic stage and the open fluid field. After the formation of pore-lined chlorite, the sweet spots developed under the protection of four mechanisms: inhibiting quartz cementation, enhancing compression resistance, protecting macropore throat and primary pores, and promoting secondary intergranular dissolved pores. When the content of chlorite in the pore lining is high (relative content > 35%), the lining thickness is moderate (4–10 μm). A high degree of wrapping and good crystallization are conducive to the formation and preservation of sweet spots.